IDENTIFIKASI BAKTERI INDIKATOR SANITASI PADA ES CAMPUR - Hati, Revita Permata (Jurnal Kesehatan Bakti Tunas Husada: Jurnal Ilmu-ilmu Keperawatan, Analis Kesehatan dan Farmasi, 2024)
In general, mixed ice is a type of ready-to-eat snack or prepared meal, sold mainly on the streets, in public places, and other types of food that are liked by the public. Mixed ice with these conditions is suspected to have a low level of sanitation, hygiene, and awareness of health risks due to foodborne illnesses. So research was carried out to determine the total contamination of coliform bacteria as an indicator of sanitation in mixed ice ready-to-eat food products. The research uses descriptive laboratory observations. A total of 12 mixed ice samples were collected using the simple random sampling method. Samples were tested using the most probable number method, which consists of a predictor test, a reinforcement test, and a complementary test. The results of the research on the samples showed the presence of coliform bacteria in all samples from the results of the predictor test, reinforcement test, and complementary tests. This can pose health risks and pose microbiological risks to consumers. It would be better for the micro-food industry and its stakeholders to improve food safety, including sanitation and hygiene. And start to apply the concept of keeping food safe from farm to table.